Generic delimitation between Fragariocoptes and Sierraphytoptus (Acari: Eriophyoidea: Phytoptidae) and a supplementary description of Fragariocoptes gansuensis with remarks on searching for mummified eriophyoid mites in herbaria under UV light - Chetverikov, Philipp E. (Zootaxa, 2016)
Generic concepts of Fragariocoptes Roivainen, 1951 and Sierraphytoptus Keifer, 1939 are discussed and the correct delimitation between these two genera is given. A supplementary description of Fragariocoptes gansuensis Wei, Chen & Luo, 2005 is included based on fresh specimens from Astrakhan, Russia and dried mummies found in old herbaria collected in 1919 from southern European Russia of the cinquefoil, Potentilla bifurca L. (Rosaceae) with pathological stem proliferation. The male of this species is described for the first time. The cuticle of eriophyoid mummies emitted a faint glow under UV light wavelength equal to 365 nm of a common UV Light-Emitting diode (LED) lamp showing that this characteristic could be useful for quickly detecting eriophyoids in old herbaria which would otherwise be almost indistinguishable against the background under the regular white light source of a stereomicroscope. This was only possible for plant material stored in appropriate conditions enabling the autofluorescent signal of the dried mite cuticle to remain strong enough for observation.